Geographical variation of cuticular hydrocarbon profiles of adult flies and empty puparia amongst three populations of Calliphora vicina (Diptera: Calliphoridae) - Kula, Canan; Amendt, Jens; Drijfhout, Falko P.; Moore, Hannah E. (Oxford University Press (OUP), 2023)
Blowflies (Diptera: Calliphoridae) are of great importance in forensic entomology and in determining the minimum post-mortem interval, as they may be the first group of insects to colonise decomposing remains. Reliable species identification is an essential prerequisite. Classically, morphological characters or DNA sequences are used for this purpose. However, depending on the species and the condition of the specimen, this can be difficult, e.g. in the case of empty fly puparia. Recent studies have shown that cuticular hydrocarbon (CHC) profiles are species-specific in necrophagous taxa and represent another promising tool for identification. However, the population-specific variability of these substances as a function of e.g. local climatic parameters has not yet been sufficiently investigated. The aim of this study was to determine the geographical variation of CHC profiles of the blowfly Calliphora vicina depending on different countries of origin. Flies were reared in the UK, Germany and Turkey in common garden experiments under ambient conditions. CHC profiles of the resulting adult flies and their empty puparia were analysed using gas chromatography-mass spectrometry. Data were visualised by principal component analysis and clustered by population. The populations of the UK and Germany, both having similar climates and being geographically close to each other, showed greater similarities in CHC profiles. However, the CHC profile of the Turkish population, whose climate is significantly different from the other two populations, was very different. Our study confirms the high potential of CHC analysis in forensic entomology but highlights the need to investigate geographical variability in chemical profiles.
Keywords: Calliphoridae; adult fly; empty puparia; cuticular hydrocarbons; GC-MS; Turkey; Germany; United Kingdom